2022
DOI: 10.3389/fpsyt.2022.853296
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends in Individuals at High Risk for Psychosis: A Bibliometric Analysis

Abstract: The study of clinical high risk for psychosis (CHR-P) has progressed rapidly over the last decades and has developed into a significant branch of schizophrenia research. Organizing the information about this rapidly growing subject through bibliometric analysis enables us to gain a better understanding of current research trends and future directions to be pursued. Electronic searches from January 1991 to December 2020 yielded 5,601 studies, and included 1,637 original articles. After processing the data, we w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Because the reenactments can be replayed and re-experienced until the correct learning is achieved, patients will confront troublesome circumstances much more easily in VR than in real life. In addition, VR offers individuals with psychiatric analysis the opportunity to implement unused helpful strategies [25]. The use of VR-supported CBT treatment to control and reduce psychotic symptoms in psychosis is a relatively new approach compared with traditional approaches, as reflected in the published literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the reenactments can be replayed and re-experienced until the correct learning is achieved, patients will confront troublesome circumstances much more easily in VR than in real life. In addition, VR offers individuals with psychiatric analysis the opportunity to implement unused helpful strategies [25]. The use of VR-supported CBT treatment to control and reduce psychotic symptoms in psychosis is a relatively new approach compared with traditional approaches, as reflected in the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…The use of VR-supported CBT treatment to control and reduce psychotic symptoms in psychosis is a relatively new approach compared with traditional approaches, as reflected in the published literature. A bibliometric analysis of research trends in people at high risk of psychosis from 1991 to 2020 identified 5,601 studies, including 1,637 original articles [25]. A review of psychological interventions for young people with psychotic experiences identified 1,449 publications [26].…”
Section: Discussionmentioning
confidence: 99%
“…CHR‐P is a common, if under‐recognized, condition, as evidenced by meta‐analytic estimates of point prevalence in the general youth population (1.7%) and in the population of youth presenting for psychiatric care (19.2%) (Salazar de Pablo et al, 2021). A recent bibliographic analysis identified 1637 unique research data publications, with two or more publications originating from 1573 separate institutions in 49 countries (Lee et al, 2022). More than 100 specialty clinics for CHR‐P have been organized in multiple countries across six continents (Kotlicka‐Antczak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…CHR-P a common, if under-recognized, condition, as evidenced by meta-analytic estimates of point prevalence in the general youth population (1.7%) and in the population of youth presenting for psychiatric care (19.2%) (Salazar de Pablo et al, 2021). A recent bibliographic analysis identified 1,637 unique research data publications, with two or more publications originating from 1,573 separate institutions in 49 countries (Lee et al, 2022). More than 100 specialty clinics for CHR-P have been organized in multiple countries across six continents (Kotlicka-Antczak et al, 2020).…”
mentioning
confidence: 99%